Câncer de cabeça e pescoço em um hospital de ensino do interior paulista: reabilitação fonoaudiológica - Figueiredo, Isabel Cristina (2015)
Introduction: Worldwidely head and neck cancer is the sixth as the most frequent cancer; 40% occurs in the oral cavity; 25% in the larynx; 15% in the pharynx and 20% in other anatomical sites. Objectives:. To analyze the association of cases of head and neck cancer and the outcome of speech rehabilitation of people with cancer of the larynx. Materials and Methods: Cross-sectional, quantitative study through survey data from medical records of patients with head and neck cancer, treated from 1989 to 2015, at Hospital de Base, São José do Rio Preto / SP, from three dimensions: socio-demographic, clinical and speech rehabilitation. The first study analyzed the correlation for cancers and variables (gender, place of origin, age and education). The second study was analyzed by univariate and multivariate techniques. Qualitative data were associated by applying the Chi-Square test. The multivariate approach through the multiple correspondence analysis enabling relations between the most important variables in the study. Results: In the first study: 52.7% were male with median age of 56 years; higher prevalence from 41 years (82.2%); 64.3% were from other cities in the state of São Paulo. Tumor predominantly affecting structures of the head and neck; presented in 53.2% of the cases. In the second study, according to the speech rehabilitation, 75.49% had alterations in the neuro-vegetative system, developed speech and voice (64.22%); of these, 22.55% esophageal voice; 21.57%) development of written communication and gestural; schooling was significantly associated with the outcome of Speech Therapy (P <0.001). The gestural communication was more frequent in patients with no schooling, improvement of dysphagia in patients with primary education, improvement of dysphagia / dysphonia and voice with electrolarynx in patients with secondary education. Most of patients with T2 and T4 tumor stage improved dysphagia and dysphonia; T1 showed improvement of dysphonia and T3 had esophageal speech development. Patients treated with chemotherapy or radiation therapy, smoker or non-smoker / drinker, with primary education and T1 stage developed esophageal voice and had dysphagia / dysphonia improved. Patients who have developed voice with electrolarynx worked in commerce or in the service sectors, age group 20-59 years with high school, nodes, metastasis and stage T4. The gestural/ writing and gestural development occurred more frequently in patients who had smoking and drinking habits and stage T3. Those who showed improvement of dysphonia had association with cordectomy (60 years or older) were working in the agricultural sector or other, with no schooling or had higher education and T2 stage. Conclusion: The optimization and diversification and positive results with new therapeutic procedures used in the treatment of these patients have showed challenges to the Speech Therapists, above all, encouraging them to intervene in areas that traditionally the effectiveness of their actions was not known to be recognized as well as evaluated.